In Vitro Evaluation of Apical Sealing Ability of HEROfill® Obturator versus Cold Lateral Condensation in Curved Root Canals - Mina Zarei; Maryam Javidi; Zeinab Kazemi; Farzaneh Afkhami (Frontiers in Dentistry, 2016)
Objectives: This study aimed to assess and compare the apical sealing ability of HEROfill® Soft-Core system and lateral condensation technique in fine curved canals using the fluid filtration method.